Fusarium graminearum produces different xylanases causing host cell death that is prevented by the xylanase inhibitors XIP-I and TAXI-III in wheat. (November 2015) - Tundo, Silvio; Moscetti, Ilaria; Faoro, Franco; Lafond, Mickaël; Giardina, Thierry; Favaron, Francesco; Sella, Luca; D'Ovidio, Renato
Highlights: Fusarium graminearum xylanases induce cell death in wheat cell cultures and in planta. F. graminearum xylanases of GH 10 and GH 11 families induce host cell death. The capacity to induce cell death and catalytic activity are unrelated features. TAXI-III and XIP-I inhibit catalytic activity and host cell death caused by xylanases. TAXI-III and XIP-I plants prevent cell death symptoms caused by xylanases. Abstract: To shed light on the role of Xylanase Inhibitors (XIs) during Fusarium graminearum infection, we first demonstrated that three out of four F. graminearum xylanases, in addition to their xylan degrading activity, have also the capacity to cause host cell death both in cell suspensions and wheat spike tissue. Subsequently, we demonstrated that TAXI-III and XIP-I prevented both the enzyme and host cell death activities of F. graminearum xylanases. In particular, we showed that the enzymatic inhibition by TAXI-III and XIP-I was competitive and only FGSG_11487 escaped inhibition. The finding that TAXI-III and XIP-I prevented cell death activity of heat inactivated xylanases and that XIP-I precluded the cell death activity of FGSG_11487 – even if XIP-I does not inhibit its enzyme activity – suggests that the catalytic and the cell death activities are separated features of these xylanases. Finally, the efficacy of TAXI-III or XIP-I to prevent host cell death caused by xylanases was confirmed in transgenic plants expressing separately these inhibitors, suggesting that the XIs could limit F. graminearum infection via direct inhibition of xylanase activity and/or by preventing host cell death.